Association between changes in loop diuretic dose and outcomes in acute heart failure - Yuta Seko; Takao Kato; Takeshi Morimoto; Hidenori Yaku; Yasutaka Inuzuka; Yodo Tamaki; Neiko Ozasa; Masayuki Shiba; Erika Yamamoto; Yusuke Yoshikawa; Yugo Yamashita; Takeshi Kitai; et al. (ESC Heart Failure, 2023)
Abstract Aims Little is known about the association between the starting of or dose changes in loop diuretics during acute heart failure (AHF) hospitalization and post‐discharge outcomes. We investigated the clinical impact of starting loop diuretics and changing the loop diuretics dose during hospitalization on post‐discharge outcomes. Methods and results From the Kyoto Congestive Heart Failure registry, 3665 consecutive patients hospitalized for HF and discharged alive were included in this study. We analysed 1906 patients without loop diuretics on admission and were discharged alive and 1759 patients who received loop diuretics on admission and were discharged alive. The primary outcome measure was all‐cause death. Of the 1906 patients without loop diuretics on admission, 1366 (71.7%) patients started loop diuretics during the index AHF hospitalization. Starting loop diuretics was not associated with lower post‐discharge mortality [adjusted hazard ratio (HR) 0.92, 95% confidence interval (CI) 0.68–1.25]. Of the 1759 patients who received loop diuretics on admission, loop diuretic dose was decreased in 23.8%, unchanged in 44.6%, and increased in 31.6% of the patients. Changes in the dose at discharge compared with no change in dose were not associated with lower risk of post‐discharge mortality (decrease relative to no change: adjusted HR 0.98, 95% CI 0.76–1.28; increase relative to no change: adjusted HR 1.00, 95% CI 0.78–1.27). Compared with no loop diuretics at discharge, a loop diuretics dose of ≥80 mg at discharge was associated with higher post‐discharge mortality risk. Conclusions In patients with AHF, we found no association between the starting of loop diuretics and post‐discharge outcomes and between dose changes and post‐discharge outcomes.